2020
DOI: 10.1002/ejlt.202000204
|View full text |Cite
|
Sign up to set email alerts
|

Different Ratios of Corn and Coconut Oil Blends in High‐Fat Diets Influence Fat Deposition without Altering Metabolic Biomarkers in Male Rats

Abstract: The effects of high‐fat diets with the recommended dietary linoleic acid (LA) intake levels on health outcomes have not been studied extensively. This study investigated the effects of high‐fat diets containing different weight ratios of coconut and corn oil with LA levels of <1.00% of energy (very low LA), 2.80% of energy (low LA), 5.80% of energy (moderate LA), and 9.70% of energy (high LA) on fat deposition and selected metabolic biomarkers of male Sprague‐Dawley rats. Their initial and terminal body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Voon and co‐workers investigated the effect of different percentages of linoleic acid contributing to very low (1%), low (2.8%), moderate (5.8%) and high (9.7%) energy in the high fat diets of male Sprague–Dawley rats fed with different ratios of corn and coconut oil blends by assessing the changes in fat deposition and selected metabolic biomarkers. The blends containing high linoleic acid caused more body weight gain and epididymal fat deposition in rats as compared to blends with low linoleic acid but high linoleic acid had no significant effect on selected metabolic indicators such as blood glucose, visfatin, leptin, serum TNF‐α, insulin, and C‐peptide levels (Voon et al, 2021). Blends of rice bran, flaxseed, and sesame oils significantly ( p < 0.0001) lowered the serum total cholesterol, LDL cholesterol, triglycerides and apoB by 3.47%, 4.16%, 10.3%, and 3.93%, respectively, in 143 patients with borderline hypercholesterolemia.…”
Section: Blending: Need and Benefitsmentioning
confidence: 99%
“…Voon and co‐workers investigated the effect of different percentages of linoleic acid contributing to very low (1%), low (2.8%), moderate (5.8%) and high (9.7%) energy in the high fat diets of male Sprague–Dawley rats fed with different ratios of corn and coconut oil blends by assessing the changes in fat deposition and selected metabolic biomarkers. The blends containing high linoleic acid caused more body weight gain and epididymal fat deposition in rats as compared to blends with low linoleic acid but high linoleic acid had no significant effect on selected metabolic indicators such as blood glucose, visfatin, leptin, serum TNF‐α, insulin, and C‐peptide levels (Voon et al, 2021). Blends of rice bran, flaxseed, and sesame oils significantly ( p < 0.0001) lowered the serum total cholesterol, LDL cholesterol, triglycerides and apoB by 3.47%, 4.16%, 10.3%, and 3.93%, respectively, in 143 patients with borderline hypercholesterolemia.…”
Section: Blending: Need and Benefitsmentioning
confidence: 99%
“…Serum ADP levels in the 1:1 and 5:1 groups were lower than those of the 20:1, NC, and Lard groups. Voon et al (2021) reported that a highfat diet supplemented with different proportions of LA (< 1%, 2.8%, 5.8%, or 9.7%) had no effects on visfatin and leptin levels. Another study reported that different n-6/n-3 PUFA ratio diets did not affect plasma leptin levels in piglets (Nguyen et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…The blends with a low-LA, MCFA diet resulted in less body weight increase than the high-LA diet. The high-LA diet resulted in considerably more fat accumulation in the epididymis [ 65 ]. The effects of a functional BO with high levels of OA (50.93%) and ALA (5.41%) on BW as compared to lard oil and PNO were evaluated.…”
Section: Effect Of Blending On Therapeutic Potentials Of Oilmentioning
confidence: 99%